Airborne nanoparticle (Nanoaerosol) sampling efficiency analysis based on filtration on TEM grid. (October 2019) - Xiang, M; Morgeneyer, M; Philippe, F; Bressot, C
Abstract: The scientific and technological issues associated with the characterization of the exposure of nano-aerosols is a huge technological challenge. Nano-aerosol measurement is a key point to characterize nanoparticle exposure. Transmission electron microscopy (TEM) coupled with energy-dispersive X-ray (EDX) is a comprehensive tool for determining size distributions and elemental compositions. Individual particle analysis allows the determination of size, morphology, specific surface, and elemental composition. Techniques allowing sampling on adapted analysis support TEM grids are of great interest to aerosol analysis: by using MPS and TEM analysis, sampling is directly and easily performed. The current paper explores the available theoretical models which assess sampling efficiency according to the chosen empirical approach. The recent studies which use this method are also briefly introduced.